(untitled) (Medical Forum Monthly, 2024)
Objective: To investigate whether ciprofloxacin induced chondrotoxicity with normal therapeutic dosage is preventable by zinc chloride if given simultaneously. Study Design: Prospective / experimental study. Place and Duration of Study: This study was conducted at the Department of Anatomy Basic Medical Science Institute Jinnah Postgraduate Medical centre Karachi from Jan 2014 Dec 2014. Materials and Methods: Ciprofloxacin & ZnCl2 was administrated to juvenile albino rats. Ciprofloxacin with a dose of 20 mg/kg body weight & ZnCl2 120 µg/100 gm body weight two times therapeutic dose for 20 days. (From day -1 to day 20 after birth.) Each animal was measured their intact bone length and were compared with similar value of control animals. The results were statistically analyzed to find out the significance. Results: Our study reveals that ciprofloxacin administered in juvenile albino rats decreased intact bone length , of Humerus right & left 9.91 ± 0.18 mm, Femur right & left 11.49 ± 0.12 mm respectively. That ciprofloxacin & ZnCl2 administration maintained the intact bone length of Humerus right & left 18.48 ± 1.25 mm, Femur right & left 14.54 ± 0.09 mm respectively. That ZnCl2 administration increased the intact bone length of Humerus right & left 14.60 ± 0.13 mm, Femur right & left 14.58 ± 0.10 mm respectively. Conclusion: The ciprofloxacin & ZnCl2 post-natal administration in juvenile albino rats affected the mean intact bone length. ZnCl2 maintained intact bone length leading to growth of the juvenile albino rats.